2014
DOI: 10.1631/jzus.b1300083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin B12 on cleft palate induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin and dexamethasone in mice

Abstract: Abstract:The purpose of this study was to investigate the effect of vitamin B 12 on palatal development by co-administration of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and dexamethasone (DEX). We examined the morphological and histological features of the palatal shelf and expression levels of key signaling molecules (transforming growth factor-β3 (TGF-β3) and TGF-β type I receptor (activin receptor-like kinase 5, ALK5)) during palatogenesis among a control group (Group A), TCDD+DEX exposed group (Group B),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 27 The combination of 10 nM TCDD and 10 ng/mL TGF-β3 also promoted MEPM cell proliferation, but the rate of cell viability was between TCDD and TGF-β3 treated alone, which might be consistent with TGF-β3 as an effective antidote to dioxin-induced MEPM cells. 28 This phenomenon was same as the effect of motilities in MEPM cells by 10 nM TCDD, 10 ng/mL TGF-β3, or combination of 10 nM TCDD and 10 ng/mL TGF-β3. 2,3,7,8-Tetrachlorodibenzo-p-dioxin inhibited the MEPM cell motility, which concurred with the fact that TCDD-mediated the inhibition of MCF-7 cell migration.…”
Section: Discussionmentioning
confidence: 65%
“… 27 The combination of 10 nM TCDD and 10 ng/mL TGF-β3 also promoted MEPM cell proliferation, but the rate of cell viability was between TCDD and TGF-β3 treated alone, which might be consistent with TGF-β3 as an effective antidote to dioxin-induced MEPM cells. 28 This phenomenon was same as the effect of motilities in MEPM cells by 10 nM TCDD, 10 ng/mL TGF-β3, or combination of 10 nM TCDD and 10 ng/mL TGF-β3. 2,3,7,8-Tetrachlorodibenzo-p-dioxin inhibited the MEPM cell motility, which concurred with the fact that TCDD-mediated the inhibition of MCF-7 cell migration.…”
Section: Discussionmentioning
confidence: 65%
“…27 The combination of 10 nM TCDD and 10 ng/mL TGF-β3 also promoted MEPM cell proliferation, but the rate of cell viability was between that of TCDD or TGF-β3 treated alone, which might be consistent with TGF-β3 as an effective antidote to dioxin-induced MEPM cells. 28 This phenomenon was same as the effect of motilities in MEPM cells by 10 nM TCDD, 10 ng/mL TGF-β3 , or a combination of 10 nM TCDD and 10 ng/mL TGF-β3 . TCDD inhibited the MEPM cell motility, which concurred with TCDD-mediated the inhibition of MCF-7 cell motility.…”
Section: Discussionmentioning
confidence: 66%
“…Water use efficiency is a value reflecting of water use capabilities. A previous study has shown that water use efficiency decreased with increasing water stress [14]. A study on Shepherdia argentea and Hippophae rhamnoides suggested, water use efficiency and soil moisture contents were cubic-curve related.…”
Section: Discussionmentioning
confidence: 89%